Assessing and enhancing work performance of sales people in direct selling industry in Chinese market - Liu, Xiaoyu (2011)
This article focuses on the field of direct selling, which is the oldest marketing method but has little attention from the scholars and does not be well understood by the public till this new century. In this dissertation, the author mainly uses qualitative research methods to solve the problem of how to assess and enhance the work performance of sales people from both company’s and team leader’s perspective of view in direct selling industry, especially in Chinese market, because there are several differences and uniqueness in this market. Some limitations and scarcity of this dissertation have raised in the end of this article, hoping that there will be some further and in-depth researches in this field.